Exploring the Potential Treatment for Mpox - Kevin Kevin; Robert Sinto; Leonard Nainggolan; Adeline Pasaribu; Sharifah Shakinah; Khie Chen Lie (Interna Publishing, 2024)
Monkeypox (Mpox) is a virus that originally infected only animals. Caused by the monkeypox virus, this infection presents with symptoms similar to smallpox. Although two years have passed since the 2022 outbreak, new cases continue to emerge monthly. Initially, human cases of mpox were confined to outbreaks in central and western Africa. However, the virus has recently spread globally, possibly due to a decline in vaccination rates. In this context, evidence for effective therapies, such as antivirals, is urgently needed. Three antivirals-tecovirimat, brincidofovir, and cidofovir-are known to have activity against the mpox virus. Their use is currently limited to expanded access for treating non-variola orthopoxvirus infections, with ongoing phase 3 trials. This review will discuss the mechanisms of action, clinical use, and efficacy of these antivirals.